A comprehensive review of weathering patterns and protective materials for stone relics - Ma, Chuang; Chin, Sim Yee; Benedict, Ashwin C.; Suriati, Ghazali; Yang, Luxin (IOP Publishing, 2025)
Stone relics are among the most important cultural heritages as they preserve a trove of cultural information of historical import. Many of these relics have sustained damage due to extensive periods weathering outdoor environment conditions causing different weathering patterns', including cracking, fracture, blistering, efflorescence, peeling, flaking and exfoliation. Among the main environmental factors causing these types of decay are water, acids, temperature fluctuations, soluble salts, and microorganisms. To preserve these stone monuments, Extensive research efforts have been devoted toward protecting these artifacts from environmental deterioration. The present paper reviews the pros and cons as well as future development perspectives of inorganic, organic, inorganic/organic composites and biological protective materials for prevention of stone relics deterioration from physical, chemical, and biological factors, which indicates that inorganic/organic composites possess obvious advantages for preventing water deterioration. Which provide future development perspectives about the protective materials.